Incidence of acute aortic dissections in patients with out of hospital cardiac arrest: a systematic review and meta-analysis of observational studies - Melo, Ryan (2022)
© 2021 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/